ANALISIS PROSES SUKSESI KEPEMIMPINAN PADA PERUSAHAAN KELUARGA ( Studi R.M Pak Abbas Pekanbaru) - Kisya Hayuni; Seno " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Leadership succession is needed in both family and non-family companies, large companies and small companies. Many family companies fail in the second generation of leadership, but many are successful, even become large after being managed by the second generation due to the success of succession planning. In order for the success of a company to be guaranteed, good leadership succession preparation is needed. This research was conducted to find an explanation of how the leadership process in family companies, especially at Pak Abbas's Restaurant. This study uses qualitative methods to find a deep understanding of the leadership succession process. To obtain data, researchers used observation, interviews and literature study as a complement. The data that can be obtained have started from the theory of leadership, succession to the theory of family companies.The results of the discussion show that the previous leader never chose a successor candidate to continue the company, but the prospective successor as a company observer has high motivation to continue the company, the former leader is only a behind-the-scenes actor who provides advice to prospective successors when they are involved as company successors. The succession process carried out includes the stage that the prospective successor has a strong responsibility to continue the company and then the successor candidate evaluation can develop the company.Keyword: Succession, Leadership, Family Company